PEMBENTUKAN MINAT BACA SISWA SEKOLAH DASAR: ANALISIS PERAN GURU - Ulayya Almast Nabila; Muhammad Abduh (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2023)
Interest in reading in students is formed because of the relationship between the teacher's role and students' reading activities in the classroom. improved, and find out the obstacles faced by teachers in increasing reading interest in class IV students at SDIT Lukman Al-Hakim Surakarta. In this study using a qualitative approach with the case study method, the validity of the data in this study with the extension of the technique of observation, technical triangulation and source triangulation. The analysis in this study uses qualitative data analysis which can make clear understanding by other people and is presented in writing in the form of a research report, from three strands, namely data reduction, data review and conclusions. The results of this study indicate that teachers play many roles in increasing students' interest in reading. In realizing a good interest in reading, the teacher has his own strategy, namely: (1) providing a stimulus, (2) providing special additional hours for students who are still constrained in reading, (3) creating a new learning atmosphere. The teacher gives freedom during lessons to do learning in the library. (4) understand the character of each learner. (5) providing motivation that reading is a means to broaden knowledge. From the five strategies used by the teacher in increasing students' interest in reading, it can be seen that the teacher acts as an educator, teacher, motivator and innovator. After the teacher becomes the four roles, the teacher will become an evaluator for his students, evaluating students at the end of learning activities, in order to improve the quality of learning.